Illustrations of bamboos in China. - Jiang, Zehui (EDP Sciences, 2022)
The characteristics of bamboo's flowering structures, culm sheaths, culms and leaves are important for the classification and identification of bamboo species. This book abounds with high-definition, informative photos, accurately demonstrating the taxonomical characteristics of bamboo's organs, particularly those of culm sheaths. Photos are supplemented with descriptions and a dozen hand-drawn, colored diagrams, rendering the book academically, artistically and practically valuable. This book is intended for bamboo taxonomists, enthusiasts, university faculty members and students alike.